Aspek Penguasaan Kosakata Bahasa Indonesia oleh Siswa Sekolah Dasar di Kota Medan - Wati Kurniawati; Deni Karsana (Badan Pengembangan dan Pembinaan Bahasa, 2020)
The first step in this research is the always dominant the noun aspect in mastering Indonesian vocabulary. The focus in this study is how the control of Indonesian vocabulary in grade 5 SD students in Medan City. There are two sub-focusses in this study: (1) what is the level of qualification and (2) aspects of Indonesian vocabulary mastery by grade 5 elementary school students. This study aims to identify control of Indonesian vocabulary by grade 5 elementary school students based on the level of qualification and aspects of Indonesian vocabulary mastery. The method used is the case study method. The population in this study were elementary school students. The sample in this study were students of grade 5 elementary school accredited A and C in Medan City who were respondents. The findings of this study were the mastery of Indonesian vocabulary by elementary students in Medan City on a good scale, namely 78%. The mastery of Indonesian vocabulary in the noun aspect that was first recognized by the students did not show the dominant aspect in this study, but the adjective aspect. AbstrakAspek nomina dalam penguasaan kosakata bahasa Indonesia (BI) selalu dominan yang menjadi langkah awal penelitian ini. Fokus dalam penelitian ini adalah penguasaan kosakata BI oleh siswa kelas 5 SD di Kota Medan. Ada dua subfokus dalam penelitian ini, yaitu bagaimana tingkat kualifikasi dan aspek penguasaan kosakata bahasa Indonesia oleh siswa kelas 5 SD. Penelitian ini bertujuan untuk mengidentifikasi penguasaan kosakata BI oleh siswa kelas 5 SD berdasarkan (1) tingkat kualifikasi dan (2) aspek penguasaan kosakata BI. Metode yang digunakan adalah metode studi kasus. Populasi dalam penelitian ini adalah siswa SD. Sampel dalam penelitian ini ialah siswa kelas 5 SD yang berakreditasi A dan C di Kota Medan yang menjadi responden. Temuan penelitian ini ialah penguasaan kosakata BI oleh siswa SD di Kota Medan pada skala baik, yaitu 78%. Penguasaan kosakata BI aspek nomina yang pertama dikenal siswa tidak menunjukkan yang dominan dalam penelitian ini, tetapi aspek adjektiva.